Characterizing cesium sorption in freshwater settings using fluvial sediments and characteristic water chemistries - Ratliff, Katherine; Mikelonis, Anne; Duffy, Jessica (Journal of environmental management, 2020)
Cesium-137 (137Cs) is a persistent contaminant that poses a significant risk to human health and the environment. Understanding the fate and transport of 137Cs following a contamination incident is necessary for effective containment and remediation. In this study, we performed experiments to investigate how Cs+ sorption processes are affected by sediment type and varying water chemistries to better understand how Cs+ is transported in freshwater settings. Sediment was collected from various river deposits along the Susquehanna River adjacent to the Safety Light Corporation United States Environmental Protection Agency (US EPA) Superfund site (Bloomsburg, PA) and characterized prior to being used in batch reactor experiments with waters characteristic of different regions in the US (Central US and Northeast US) and with three different cation types (Mg2+, Na+, and K+) over a range of ionic strengths. Greater amounts of Cs+ sorption occurred with increasing sediment mud (silt and clay) content, although no major differences in sorption between the Central and Northeast US water types were observed. At an ionic strength (I) of 10 mM, K+ inhibited Cs+ sorption most effectively, followed by Mg2+, with Na+ having little effect on Cs+ sorption over the range of ionic strengths tested (I = 0.1, 1, and 10 mM). Our findings indicate that for the representative freshwater conditions tested here, sediment type (e.g., clay fraction) has a greater influence on Cs+ sorption processes than water chemistry. Additional reactions or processes occurring in relatively fresh water could buffer cation competition for sorption sites. Conducting experiments using site-specific sediment samples and water chemistries is useful for predicting Cs+ sorption and mobility in distinct environmental settings, particularly when the level of Cs+ contamination is high and if the waste or contaminated (or receiving) waters have a relatively high ionic strength. •Experiments with site-specific sediment and water types useful for predicting Cs+ mobility.•Cs+ sorption higher in sediments with greater mud (silt and clay) content.•Cation experiments showed Cs+ sorption inhibited by K+ > Mg2+ > Na+.•Freshwater chemistry has relatively minor impact on sorption processes.